Impact of Pelvic Floor Muscles Function and Exercises of Women: Exploring the Impact and Exercises of Pelvic Floor Muscles in Women's Health (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In modern times, urinary incontinence is a frequent symptom, affecting 7–37 of women aged 20–39 and 9–39 of women over 60. Incontinence is more likely in women who are pregnant or who have given birth naturally. Introduce pelvic floor muscles, describe their function, examine perineum muscles, gauge pelvic floor muscular strength with stretches, and draw a final conclusion in this article.